Analisis Perlakuan Pendapatan Berdasarkan Pernyataan Standar Akuntansi Keuangan No. 72 Pada PT. Bosowa Berlian Motor Manado - Saraswati Rahayu; Stanly W. Alexander; Priscillia Weku (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Revenue is one of the signs of profit that is reported in the income statement, therefore an appropriate method of income treatment is needed so that transactions can be recognized, measured and disclosed accurately. The purpose of this research is to find out and analyze how the income treatment based on PSAK No. 72 At PT. Bosowa Berlian Motor Manado. The type of research used is descriptive qualitative. Data collection techniques using interviews and documentation. Based on the results of the study, revenue recognition is in accordance with PSAK No. 72 which stipulates that revenue is recorded using the accrual basis and are recognized when the goods or services are rendered. The measurement of revenue is in accordance with PSAK No. 72 which stipulates that income is measured based on the number of invoices in the form of invoices calculated at an agreed rate with an acceptable fair value measurement unit. However, the disclosure is not fully in accordance with PSAK No. 72 because there is some undisclosed information such as revenue segregation by category such as payment method and customer.